Attitude control actuator scaling laws for orbiting solar reflectors. Issue 1 (1st January 2023) - Viale, Andrea; McInnes, Colin R.
Abstract: The rapid evolution of in-orbit manufacturing will enable the fabrication of low-cost, large-scale space structures. In particular, the use of 3D printing technologies will remove traditional payload constraints associated with launch vehicles, due to fairing size and launch loads, thus allowing the construction of larger and lighter structures, such as orbiting solar reflectors. These structures will require efficient attitude control systems, able to provide the necessary torque for maneuvers and to counteract perturbations, such as gravity gradient and solar radiation pressure. In this paper, a top-level overview of actuator performances for orbiting solar reflectors is provided, and scaling laws associated with the required actuator mass and input power are developed. For each class of actuator, upper bounds on the maximum size of the structure which can be effectively controlled are presented. The results can also be extended to other classes of large planar Earth-pointing structures such as solar power satellites, solar sails, or large antennae.